1985
DOI: 10.1111/j.1432-1033.1985.tb09151.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of 2-oxoaldehyde in yeasts. Purification and characterization of NADPH-dependent methylglyoxal-reducing enzyme from Saccharomyces cerevisiae

Abstract: An enzyme catalyzing the reduction of methylglyoxal was isolated from Saccharomyces wrevisiae and its enzymatic properties were analyzed. The enzyme, specifically eluted from a blue-dextran -Sepharose CL-6B column by the substrate, methylglyoxal, was homogeneous on polyacrylamide gel electrophoresis. The enzyme consisted of single polypeptide chain with a relative molecular mass of 43000. The enzyme was glycoprotein and contained 6.6% carbohydrate. NADPH was specifically required for activity and the K, for NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 10 publications
2
33
0
Order By: Relevance
“…Kinetic measurements have shown that YKER-IV only is effective for the reduction of ex-keto esters at low substrate concentrations. The MichaelisMenten constant of YKER-IV is explicitly smaller than those of other two enzymes, YKER-II and -V. YKER-IV showed similar properties to those of methylglyoxal reductase 16 ) and ketopantoyllactone reductase 13 15) from the viewpoint of substrate specificity and molecular mass of these enzymes. Both enzymes were isolated from Saccharomyces cerevisiae.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Kinetic measurements have shown that YKER-IV only is effective for the reduction of ex-keto esters at low substrate concentrations. The MichaelisMenten constant of YKER-IV is explicitly smaller than those of other two enzymes, YKER-II and -V. YKER-IV showed similar properties to those of methylglyoxal reductase 16 ) and ketopantoyllactone reductase 13 15) from the viewpoint of substrate specificity and molecular mass of these enzymes. Both enzymes were isolated from Saccharomyces cerevisiae.…”
Section: Discussionmentioning
confidence: 84%
“…Molecular mass of methyl glyoxal red uctase is reported to be 25.7 kDa by Sephadex 0-150 gel filtration and 43 kDa by SDS-PAOE. 16 ) The molecular mass of ketopantoyllactone reductase has been estimated to be 27.4 kDa for Form A and 27 kDa for Form B based on the results from gel filtration.14) Catalytic activities for the reductions of methylglyoxal, phenylglyoxal, and ketopantolactone by YKER -IV are very large compared to those for ex-keto esters. Kms ofYKER-IV for phenylglyoxal and methyl glyoxal were 0.651 mM and 1.93 mM, respectively and these Kms are similar to those of methyl glyoxal reductase for phenylglyoxal (1.54mM) and methyl glyoxal (5.88mM).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MG reductase activity was determined spectrophotometrically as described [31] with minor modification: using 1 mM MG as substrate and 50 mM sodium phosphate buffer, pH 7.4 at 37°C, as the assay buffer. D-Lactate was measured by endpoint enzymatic assay with microplate fluorimetry [32].…”
Section: Characterisation Of the Glyoxalase System And Methylglyoxal mentioning
confidence: 99%
“…To elucidate the function of methylglyoxal in cell proliferation, we have examined the metabolic fate of methylglyoxal in yeast Saccharomyces cerevisiae cells and found an alternative route for methylglyoxal degradation besides the glyoxalase system consisting of glyoxalase I and glyoxalase 11. In this route, methylglyoxal is converted into L-lactaldehyde by NADPH-dependent methylglyoxal reductase [6] and L-lactaldehyde is then converted to L-lactate by NAD-dependent L-lactaldehyde dehydrogenase [7]. The NADPH-dependent methylglyoxal reductase has been found in all the microbial (Escherichia, Bacillus, Pseudomonas species, Actinomycetes and molds) and mammalian (brain, liver, heart, spleen and kidney of rat) cells at a considerably high activity and was thought to have a significant role in methylglyoxal metabolism in combination with the glyoxalase system (unpublished results).…”
mentioning
confidence: 99%